The South American species of Chalcis Fabricius (Hymenoptera: Chalcididae) - Saguiah, Pâmella Machado; Molin, Ana Dal; Tavares, Marcelo Teixeira (Zootaxa, 2020)
Chalcis Fabricius (Hymenoptera: Chalcididae) currently includes over 50 described species, most of them from temperate regions of the Northern Hemisphere. Prior to the present study, only Chalcis pilicauda (Cameron) had been recorded from South America. The examination of specimens collected in Argentina, southern Bolivia, Brazil, Ecuador, Paraguay, and Uruguay allowed the description of six new species: C. boi Saguiah & Tavares sp. nov., C. danunciae Saguiah & Tavares sp. nov., C. intervalensis Saguiah & Tavares sp. nov., C. periotoi Saguiah & Tavares sp. nov., C. quechua Saguiah & Tavares sp. nov., and C. winstonae Saguiah & Tavares sp. nov. Chalcis pilicauda is redescribed, and C. ornatifrons (Cameron) stat. rev. is removed from synonym under C. pilicauda and re-established. An identification key for South American species is presented.